Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. ta có \(3^{102}=3^{3\times34}=27^{34}>25^{34}=5^{2\times34}=5^6\text{ vậy }3^{102}>5^{68}\)
b. ta có \(C=1+2+..+2^{2017}\text{ nên }2C=2+2^2+...+2^{2018}\)
lấy hiệu ta có : \(C=\left(2+2^2+..+2^{2018}\right)-\left(1+2+..+2^{2017}\right)=2^{2018}-1< 2^{2018}\)
Vậy \(C< 2^{2018}\)
c. dễ thấy \(C>\frac{1}{2}=F\)
d. ta có \(5G=1+\frac{1}{5}+..+\frac{1}{5^{2016}}\Rightarrow4G=1-\frac{1}{5^{2017}}\)hay \(G=\frac{1}{4}-\frac{1}{4\times5^{2017}}< \frac{1}{4}=H\text{ hay }G< H\)
Đặt \(A=\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}+\frac{1}{3^{100}}\)
\(3A=3\left(\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}+\frac{1}{3^{100}}\right)\)
\(3A=1+\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}\)
\(3A-A=2A\)
\(=1+\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}-\left(\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}+\frac{1}{3^{100}}\right)\)
\(=1+\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^{99}}-\frac{1}{3^1}-\frac{1}{3^2}-\frac{1}{3^3}-...-\frac{1}{3^{99}}-\frac{1}{3^{100}}\)
\(=1-\frac{1}{3^{100}}\)
\(2A=1-\frac{1}{3^{100}}\Rightarrow A=\frac{1-\frac{1}{3^{100}}}{2}< \frac{1}{2}\)
\(\Rightarrow A< \frac{1}{2}\)
3C=1+1/3+1/32+........+1/321
3C-C=2C=1+1/3+1/32+........+1/321-(1/3+1+32+1/33+...+1/322)
2C=1-1/322
C=1/2-1/322/2<1/2
Vậy C<1/2
\(\frac{C}{3}=\frac{1}{3^2}+\frac{1}{3^3}+\frac{1}{3^4}+...+\frac{1}{3^{100}}\)
\(\frac{2C}{3}=C-\frac{C}{3}=\frac{1}{3}-\frac{1}{3^{100}}\)
\(2C=1-\frac{1}{3^{99}}\Rightarrow C=\frac{1}{2}-\frac{1}{2.3^{99}}< \frac{1}{2}\)
3A = 1+1/3+1/3^2+...+1/3^99
3A-A=(1+1/3+...+1/3^99)-(1/3+1/3^2+...+1/3^99)
2A= 1-1/3^99
A = (1-1/3^99)/2 < 1/2
=> A < 1/2
b) Đặt \(C=\frac{1}{4}+\frac{1}{4^2}+....+\frac{1}{4^{1000}}\)
\(\frac{1}{4}A=\frac{1}{4^2}+\frac{1}{4^3}+.......+\frac{1}{4^{1001}}\)
\(A-\frac{1}{4}A=\left(\frac{1}{4^2}-\frac{1}{4^2}\right)+\left(\frac{1}{4^3}-\frac{1}{4^3}\right)+.....+\frac{1}{4}-\frac{1}{4^{1001}}\)
\(\frac{3}{4}A=\frac{1}{4}-\frac{1}{4^{1001}}\)
Đến đây Đặt \(\frac{3}{4}B=\frac{1}{4}\)
Ta có: \(\frac{3}{4}A<\frac{3}{4}B\) \(\rightarrow A
Đặt \(A=\frac{2^{2017}+1}{2^{2018}+1}\Rightarrow2A=\frac{2^{2018}+2}{2^{2018}+1}=\frac{2^{2018}+1+1}{2^{2018}+1}=1+\frac{1}{2^{2018}+1}\)
\(B=\frac{2^{2018}+1}{2^{2019}+1}\Rightarrow2B=\frac{2^{2019}+2}{2^{2019}+1}=\frac{2^{2019}+1+1}{2^{2019}+1}=1+\frac{1}{2^{2019}+1}\)
Vì \(2^{2019}+1>2^{2018}+1\Rightarrow\frac{1}{2^{2019}+1}< \frac{1}{2^{2018}+1}\)
\(\Rightarrow2A>2B\Rightarrow A>B\)
A = 1/3 + 1/32 + ...................+ 1/32018
3x A = 1 + 1/3 + 1/32 +...+1/32017
3A - A = 1 - 1/32018
2A = 1- 1/32018 < 1
⇔ A < \(\dfrac{1}{2}\)